Follow-up of newborns at risk: integrativa literature review (Research, Society and Development, 2020)
The objective was to analyze the scientific productions available in the literature on the care of newborns at risk in the context of the follow-up program. This is an integrative literature review carried out in the CINAHL, LILACS, MEDLINE / PubMed, Scopus and Web of Science databases, in February 2020. Twelve studies were selected, nine of which were quantitative and three qualitative, grouped into three categories: health conditions of newborns monitored by the follow-up program; factors that influence adherence and dropout from the follow-up program; nursing care in the follow-up program. This review points to a notable need to expand activities on the persistence of care for newborns discharged from neonatal units and on the follow-up program, in order to be subsidiary and can overcome the difficulties pointed out by the researches analyzed.